KONSEP DAN TUJUAN PENDIDIKAN ISLAM - Rusmin B., Muhammad (Inspiratif Pendidikan, 2017)
Education is a process of activities toward a goal because a job without a clear purpose will cause a lack of determination in the process. Especially in the educational process that is aimed at the life of the psychology of learners who are still at the stage of development, then the goal is the most important factor in the educational process. Therefore with a clear purpose, the subject matter and methods used, got the pattern and the contents and the potentialities that are in line with the ideals contained in the purpose of education. The purpose of Islamic education contains in it a certain values in accordance with the views of Islam itself which must be realized through a process that is directed and consistent by using various physical and nonphysical facilities that are equal to its values.